Over Expressed TKTL1, CIP-2A, and B-MYB Proteins in Uterine Cervix Epithelium Scrapings as Potential Risk Predictive Biomarkers in HR-HPV-Infected LSIL/ASCUS Patients - Chiarini, Anna; Liu, Daisong; Rassu, Mario; Armato, Ubaldo; Eccher, Claudio; Dal Prà, Ilaria (Frontiers in Oncology, 2019)
Oncogenic human papilloma viruses (HPVs) promote human cervical carcinoma (HCC) development, the fourth most common feminine cancer. A lengthy oncodevelopmental phasehistopathologically defined as Cervical Intraepithelial Neoplasia (CIN) stages 1-to-3, or cytologically as Low- or High-grade Squamous Intraepithelial Lesions (LSIL or HSIL) or Atypical Squamous Lesions of Undetermined Significance (ASCUS)precedes the final HCC outcome. HCC screenings through cytology and HPV DNA genotyping are regularly performed in Western countries. Faulty cytology screening or incomplete genotyping or patient’s noncompliance with indicated follow-ups can let slip a diagnosis of oncoprogression. The well-known problematic triage of LSIL/ASCUS patients could be solved if novel biomarker tests would flank cytology and HPV genotyping. Here, anonymized leftovers of fresh cervical epithelium scrapings from twice (LSIL/ASCUS and high-risk (HR)-HPV DNA)-positive and twice (Pap smear- and HPV DNA)-negative (control) patients, served to assess the biomarker worth of three HCC-related proteins, i.e., B-MYB (or MYBL2), Cancerous Inhibitor of PP2A (CIP-2a), and transketolase-like1 (TKTL1). Anonymity of the leftovers was strictly preserved along all the steps of the study and storage at -80°C in an ad hoc freezing solution, protein extraction, standardized Western immunoblotting, and protein band densitometry analysis were all performed under blind conditions. Only after completing the tests on all the scrapings, their anonymous yet code-corresponding HPV-genotyping and cytology data allowed to categorize them as belonging to the twice-positive or twice-negative groups. Descriptive statistics showed that the three proteins levels significantly increased in the twice-positive vs. twice-negative scrapings. Diagnostic ROC curve analysis identified Optimal Decision Thresholds and hence showed that TKTL1 and CIP-2a proteins are useful biomarkers (Sensitivity, 0.91-0.93; Specificity, 0.77-0.83) of an ongoing HR-HPV-driven oncogenesis. Logistic Regression coupled with Likelihood-Ratio Tests confirmed that a highly significant relation exists between increasing TKTL1/CIP-2a protein levels and HR-HPV-driven oncoprogression. Besides this proof of concept drawn from unknown samples, our data show that cytology, HPV DNA genotyping, and TKTL1/CIP-2a assays can be performed on the same cervical epithelium scrapings. This would simplify and speed up the management of LSIL/ASCUS patients by discriminating those immediately needing colposcopy referral from those eligible for a delayed follow-up.